2008
DOI: 10.1143/jjap.47.8880
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Phase Transitions and Piezoelectric Properties in Lead-Free (K,Na,Li)NbO3–BaTiO3 Ceramics

Abstract: In this manuscript, we report the polymorphic phase transitions, structural changes and piezoelectric properties of alkali niobate based lead-free ceramics. The phase transitions were characterized as a function of alkali niobate content at room temperature. The results clearly demonstrate that in this system high piezoelectric properties are achieved for a specific fraction of ferroelectric orthorhombic (O) and tetragonal (T) phases. Using Rietveld and powder diffraction analysis, a correlation was establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 17 publications
4
34
0
Order By: Relevance
“…However, an orthorhombic symmetry with a ≈ c > b is usually characterized by the splitting of (2 0 0)/(0 0 2) and (0 2 0) peaks owing to the difference between a and b. Compared to (0 2 0) line, the (2 0 0) [15], where I Small-Brag and I Large-Brag are the intensities of (2 0 0) peaks with small Brag angles and large Brag angles, respectively, and SI T and SI O are the sums of peak intensities for tetragonal and orthorhombic phases, respectively, as summarized in Table 1. It can be found that the two-phase coexistence zone covers a broad composition range, which exhibits a different characteristic from that of an MPB.…”
Section: Resultsmentioning
confidence: 99%
“…However, an orthorhombic symmetry with a ≈ c > b is usually characterized by the splitting of (2 0 0)/(0 0 2) and (0 2 0) peaks owing to the difference between a and b. Compared to (0 2 0) line, the (2 0 0) [15], where I Small-Brag and I Large-Brag are the intensities of (2 0 0) peaks with small Brag angles and large Brag angles, respectively, and SI T and SI O are the sums of peak intensities for tetragonal and orthorhombic phases, respectively, as summarized in Table 1. It can be found that the two-phase coexistence zone covers a broad composition range, which exhibits a different characteristic from that of an MPB.…”
Section: Resultsmentioning
confidence: 99%
“…One of the strategies for achieving a higher piezoelectric response has been to modulate the composition such that the O/T transition lies close to room temperature. 73 Another strategy adopted for designing lead-free compositions is based upon the trend between the atomic weight ratio of A to B sites ( R w = W a / W b ) and the longitudinal piezoelectric constant d 33 , as shown in Figure 7b . 74 It can be observed that 1/ R w for KNN ceramics (for Na/K ratio of 0.5) is similar to R w for PZT ceramics at the MPB composition, and both of these materials exhibit high piezoelectric response.…”
Section: Lead-free Piezoelectric Fi Lmsmentioning
confidence: 99%
“…To understand the structure -property correlation in KNN-based ceramics Ahn et al studied the interdependence of piezoelectric coefficient d 33 , tetragonal to orthorhombic transition temperature (T oÀt ) and fraction of tetragonality [80]. This analysis was conducted for three different systems namely KNN-BaTiO 3 (KNN-BT), KNN-LiNbO 3 (KNN-LN) and (K,Na,Li)NbO 3 -BaTiO 3 (KNLN-BT).…”
Section: Dopant Engineeringmentioning
confidence: 99%